Penggambaran Ulang Pahlawan Pewayangan Gatotkaca dalam Komik Digital @Garudayana - Yehezkiel Tarnama Hasudungan Siahaan; Dewi Sad Tanti (Program Studi Ilmu Komunikasi Universitas Mataram, 2021)
Garudayana digital comics are comics that tell about characters in the Javanese wayang world, such as Gatotkaca. This study aims to find out how the depiction of heroes in wayang with those in digital comics. The theory used in this research is message theory. The paradigm in this research is constructivist with the semiotic method of Charles Sanders Pierce. Pierce's triangular theory of meaning explains the relationship between the signs in the digital comic so that it can be seen how the meaning and depiction are produced in the digital comic. The results of this study indicate that the depiction of the hero character Gatotkaca in wayang in this digital comic is quite the same as that in wayang. Things such as the clothes used to the things of strength and expression depicted in this digital comic have almost represented the character of Gatotkaca in the wayang world.